Investigation of influence of heat treatment on mechanical strength of FDM printed 3D objects - Jo, Wonjin; Kwon, O-Chang; Moon, Myoung-Woon (EMERALD GROUP PUBLISHING LTD, 2018)
Purpose - Despite the rapid development of fused deposition modeling (FDM), the insufficient mechanical strength of the printed objects is one of the biggest stumbling blocks for practical applications. Therefore, the purpose of this study is to emphasize on the importance of homogeneous heating condition and heating effect in the improvement of the mechanical strength of objects. Design/methodology/approach - The authors first analyze the problem of the present heating system under a heating bed and chamber by using a commonly used home FDM printer. Next, they investigate the heating effect on the mechanical properties of FDM-printed objects in terms of layer thickness, heating duration and additional pressure with heating. The printed objects are treated in a mold by forced convection heating. Findings - As the layer thickness decreases, the mechanical performance of the FDM-printed objects is remarkably enhanced by thermal heating because of the result of strong interfacial bonding among the rasters and layers. In addition, longer heating duration and higher external pressure play pivotal roles in the mechanical performance by reducing voids in the internal structure of the printed objects, leading to high densification and complete filling at the interfaces. Originality/value - The present findings, for the first time, show that controlling uniform heat transfer is highly important for the mechanical performance of FDM three-dimensional printed objects. The authors suggest that the future developed home or personal FDM types should consider the homogeneous temperature environment during the printing process by properly heating the inside chamber. In addition, the results indicate the effectiveness of heating and pressure treatment to the objects for the reinforced mechanical performance and better surface finish.